Estudio de prevalencia de las patologías con resolución quirúrgica más comunes en una clínica veterinaria de grandes animales enfocado en el caballo criollo colombiano (2024)
This study was made in Cajica with the objective of having more knowledge about which pathologies are more likely to present in a horse criollo colombiano with a surgical resolution. 52 medical records were found in the clinic located in Cajica, the pathology with more incidence was hyperflexion of the hind limbs or stringhalt compared to the other pathologies registered on the clinic. The conclusion was that the criollo colombiano horse has more incidence in this pathology because of the way he flexes his limbs.